Current trends of monetary policy of Ukraine - Shvayko , M. L. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2017)
In the article current trends of monetary policy of Ukraine are considered. For this purpose the following key questions are considered: essence specification, evolution of development and main instruments of monetary policy; definition of the basic purpose, tendency and feature of its realization in modern conditions; a specification of the perspective directions of development of monetary policy of Ukraine for the purpose of its optimization; research of activity of the NBU as basic conductor of monetary policy. It is noted that in modern conditions the basic purpose of monetary policy of Ukraine is ensuring price stability by observance of the quantitative purposes concerning inflation, and change of a key interest rate of monetary policy, as it has the most significant effect on a condition of the monetary and credit market, acts as the main instrument of its realization. Also as the medium-term purposes of monetary policy NBU defines observance of the mode of a floating exchange rate, transparency of activity of National bank and its institutional, financial and operational independence. The analysis of statistical data concerning dynamics of discount rate of the NBU and an index of inflation is carried out. The tendency to their decrease is noted, and also the thesis about continuation of moderate mitigation of monetary policy in the medium term for the purpose of activation of process of crediting and assistance to economic growth is reasonable.